Design and Build a System to Minimize the Impact of Toluene Exposure on IoT-Based Workshop Workers - Galang Gastiadi; M. Nanak Zakaria; Ahmad Wilda Yulianto (Jurnal Jaringan Telekomunikasi, 2022)
Toluene is one type of organic solvent that is widely used in industry. Organic solvents can have a negative impact on health when exposed to the human body through inhalation (breathing), digestion (swallowing) and adsorption (skin contact). This compound is widely used as a basic material for solvents, dyes, paints, resins, perfumes, nail polish, gasoline, glue, solvent thinner, immersion ink, and printing. The impact on each human will vary depending on the concentration, duration and toxicity of the solvent. The effects of exposure are generally long-term and short-term. Short-term effects include respiratory complaints and eye irritation in exposed humans. An ESP32 microcontroller, HCHO sensor, and DHT11 sensor were used in this study to construct a system to lessen the effects of toluene exposure on workshop personnel. Temperature and humidity sensors picked up by DHT11 have an average value for each node. Each node's average value for the temperature and humidity sensors detected by DHT11 is available. The average error value is categorized as accurate and good for nodes A and B, which are separated by 2 meters and 4 meters, respectively. Due to the DHT11's error rates, the temperature range is 20C and the humidity range is 5% RH.